Setting the Set Point: Initial Predictors of Life Satisfaction in Early Adulthood - Eileen Trzcinski; Elke Holst (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
In this article, we examine the patterns of association among a number of different factors that may contribute to differences in the initial baseline level of subjective well-being among young people in transition to adulthood. By examining the nature and patterns of these associations, we intend to identify potential areas where strategies may be developed?at the individual, micro, or macro level of policy?to influence the determinants of the baseline level of subjective well-being that are not attributable to genetic or inherited traits.
Keywords: 330